2016
DOI: 10.1007/s11664-016-4421-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy Study of 4-ATP on Gold Nanoparticles for Basal Cell Carcinoma Fingerprint Detection

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk AbstractThe surface-enhanced Raman (SER) signal of 4-aminothiolphenol (4-ATP) based on the surface of gold nanoparticles col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Validation by spectroscopy and confocal microscopy showed that the SERS probe was capable of cellular imaging with high cytocompatibility for HepG2 and A549 cells. Quynh et al used 4-aminothiolphenol (4-ATP)-attached AuNPs to detect basal cell carcinoma (BCC) of the skin [ 37 ]. Au-4ATP was prepared by a wet chemical process and, for antibody conjugation, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) was mixed with BerEP4, then added to the Au-4ATP solution.…”
Section: Photoimagingmentioning
confidence: 99%
“…Validation by spectroscopy and confocal microscopy showed that the SERS probe was capable of cellular imaging with high cytocompatibility for HepG2 and A549 cells. Quynh et al used 4-aminothiolphenol (4-ATP)-attached AuNPs to detect basal cell carcinoma (BCC) of the skin [ 37 ]. Au-4ATP was prepared by a wet chemical process and, for antibody conjugation, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) was mixed with BerEP4, then added to the Au-4ATP solution.…”
Section: Photoimagingmentioning
confidence: 99%
“…After being conjugated with Fe 3 O 4 -Ag-antiCD34, (C) shows that no green luminescent CD45+ cells were observed, and (D) shows that only the red luminescent CD34+ cells were isolated from the bone marrow samples. The EDC catalyst enhanced the reaction of the amino group on the surface of Fe 3 O 4 -Ag with the carboxyl group of the ECD-antiCD34 antibody molecules [39]. The conjugated product, Fe 3 O 4 -Ag-antiCD34 nanoparticles, emits red light under the excitation of 494 nm incident light.…”
Section: Multifunctional Silver Nanoparticles and Their Applicationsmentioning
confidence: 99%
“…Thus SERS has attracted great interest in the biolabeling field because significant enhancement of the labeling signals of molecular vibrations on the metallic nanoparticles surface can be obtained. Quynh et al (2016) studied surface-enhanced Raman (SER) signal of 4-ATP that was linked to the surface of gold nanoparticles conjugated with skin carcinoma cell antibody BerEP4. Gold nanoparticles with sizes ranged from 2 to 5 nm were prepared by a wet-chemical method using CTAB.…”
Section: Basal Cell Carcinoma Fingerprinted Detectionmentioning
confidence: 99%
“…7.2, only A2, B2, C2, and D2 regions can be definitely considered as the cancer areas, while A1, B1, C1, and D1 may assigned as the position of hair follicles where the cell concentration is higher than in other parts. Quynh et al (2016) pointed out that, while the whole SER map collecting time should be longer than 2 hours (the collecting time of each spectrum was nearly 5 seconds), the fingerprinted image using peak height at 1075 cm 21 can be observed in around 5 minutes. Hence, this method may represent a solution for quick diagnosis, even during operation.…”
Section: Basal Cell Carcinoma Fingerprinted Detectionmentioning
confidence: 99%